Fungos micorrízicos e Azospirillum no desenvolvimento do trigo em solo contaminado com cobre - Turchetto, Ricardo (2021)
Copper (Cu) is a micronutrient considered essential for plants, however, the addition of metal in the soil by human activities, makes this element potentially polluting and toxic to agricultural species. The dynamics of copper in the soil is influenced by the physical and chemical characteristics of the soil as well as the activity of symbiotic microorganisms associated with different cultures. Thus, the general objective of this work was to analyze the influence of different soil textures, species of mycorrhizal fungi and plant growth promoting bacteria on the tolerance and accumulation of copper in wheat plants grown in soil contaminated with copper. To meet the objective, three scientific studies were developed, the first of which aimed to assess the influence of soil texture on copper toxicity and the development capacity of wheat in soil contaminated with this metal; the second to evaluate the effect of inoculation of three species of mycorrhizal fungi on the growth and accumulation of copper in wheat plants in soil contaminated with copper; and in the third, to determine the influence of the use of mycorrhizal fungi associated with a genus of bacteria that promotes plant growth in the growth and accumulation of copper by the cultivation of wheat grown in soil contaminated with copper. The results showed that the wheat culture is negatively influenced by the addition of copper to the soil, and its content is affected by the soil texture. Sandy soils favor the translocation of copper to the wheat grain in areas contaminated with this metal. The bioconcentration and bioaccumulation of copper in the wheat crop is superior in soil with a texture of 17.5%. The mycorrhizal isolates Acaulospora Colombiana and Gigaspora Margarita provide greater height, root length and specific surface area and lower copper content in the grain in wheat. Mycorrhizal fungi allow a higher content of copper in the roots and consequently less mobilization of this metal to the aerial part and grains of wheat. There is an antagonistic effect of the co-inoculation of A. brasilense on the colonization of wheat roots by mycorrhizal fungi of the genus A. colombiana and G. margarita. Co-inoculation A. Colombiana / A. Brasilense provides higher copper content in the aerial part of the wheat.